The influence of online customer reviews, discounts, and cod features on purchase decisions for jiniso products in tiktok shop for gen z - Septiyana Eka Cahya Ningrum; Edy Purwo Saputro (Institute of Computer Science (IOCS), 2026)
This study analyzes the effects of Online Customer Reviews, Discounts, and Cash on Delivery (COD) features on Generation Z’s Purchase Decisions for Jiniso products on TikTok Shop. Despite the platform’s rapid growth, prior research has not sufficiently clarified which factors most strongly shape Gen Z’s purchasing behavior in short-video–based social commerce, creating a gap in understanding the relative importance of reviews, promotional incentives, and payment flexibility. This study addresses that gap by simultaneously examining these three determinants within a single predictive model. Using a quantitative design, data were collected from 105 purposively selected respondents aged 17 and above in the Solo Raya region through structured questionnaires. Key variables were measured through indicators of review credibility, discount characteristics, COD convenience and security, and decision-making stages. Data were analyzed using PLS-SEM with SmartPLS 3.0 to assess reliability, validity, and hypothesis significance. The findings show that Online Customer Reviews and COD features exert a significant positive influence on Purchase Decisions, whereas Discounts demonstrate a positive but non-significant effect. These results highlight the dominant role of credible reviews and flexible payment methods in shaping Gen Z consumer behavior on TikTok Shop and provide practical guidance for optimizing marketing strategies on emerging social commerce platforms.